The Effect of Corporate Governance on Profitability as A Moderating Variable - Wangi, Bunga Mega; Komalasari, Agrianti; Suhendro, Saring (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study investigates the impact of corporate governance on profitability, with Corporate Social Responsibility (CSR) serving as a moderating variable, focusing on chemical, pharmaceutical, and traditional medicine companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023. Using panel data regression with a fixed effect model, the research finds that both independent commissioners and audit committees have a significant positive influence on profitability. The moderated regression analysis further reveals that CSR positively moderates the relationship between independent commissioners and profitability, while it negatively moderates the effect of audit committees on profitability. The findings suggest that enhanced corporate governance mechanisms, particularly the roles of independent commissioners and audit committees, contribute significantly to improved profitability. However, the varying moderating effects of CSR highlight the complexity of corporate governance dynamics. The study is limited by its five-year scope, industry-specific focus, and reliance on secondary data, suggesting that future research should expand the observation period, incorporate other sectors, explore additional moderating variables, and integrate primary data. These findings contribute valuable insights into the corporate governance practices within Indonesia's pharmaceutical sector.